1994
DOI: 10.3109/08977199409046915
|View full text |Cite
|
Sign up to set email alerts
|

The Immunolocalization of Basic Fibroblast Growth Factor in the Mouse Uterus During the Initial Stages of Embryo Implantation

Abstract: Mammalian embryo implantation involves a series of complex interactions between maternal and embryonic cells. Uterine polypeptide growth factors may play critical roles in these cell interactions. Basic fibroblast growth factor (basic FGF) is a member of a family of growth factors. This growth factor may be potentially important for the process of embryo implantation because it (a) is stored within the extracellular matrix and is thus easily available during embryo invasion, (b) is a potent modulator of cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Thus, decidual HPSE is likely to cleave the HS components of the basal laminae as well as decidual HSPGs, facilitating embryo implantation by partially degrading or remodeling the extracellular matrix. In addition, HPSE is likely to release HSbinding growth factors involved in promoting embryo development or in the decidualization process [6,46,[55][56][57]. The activity assay indicated that the increase in HPSE activity greatly exceeded the increase in mRNA.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, decidual HPSE is likely to cleave the HS components of the basal laminae as well as decidual HSPGs, facilitating embryo implantation by partially degrading or remodeling the extracellular matrix. In addition, HPSE is likely to release HSbinding growth factors involved in promoting embryo development or in the decidualization process [6,46,[55][56][57]. The activity assay indicated that the increase in HPSE activity greatly exceeded the increase in mRNA.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, pseudo pregnancy selectively induces FGF2 mRNA in mesometrial tissue in rats and there is greater FGF2 immunolocalized in isolated mesometrial decidua cells than isolated anti-mesometrial cells [99]. FGF2 protein distribution also demonstrates temporal and spatial changes during the peri-implantation period in the rat [100].…”
Section: Fgf2 (Bfgf)mentioning
confidence: 94%
“…A role for FGFR-1 signaling in suppressing premature capacitation is plausible as bFGF has been identified in the uterus of many species including humans, monkeys, pigs, mice and rats (Ferriani et al, 1993;Gupta et al, 1997;Reynolds et al, 1998;Rider et al, 1997;Samathanam et al, 1998;Sangha et al, 1997;Wordinger et al, 1994). We hypothesize that binding of bFGF (or an equivalent ligand) to FGFR-1 leads to activation of the PI3K pathway and the subsequent phosphorylation of an as yet to be identified 'master controller of capacitation' (MCC) (Fig.…”
Section: Discussionmentioning
confidence: 99%